Tannic acid attenuates intestinal oxidative damage by improving antioxidant capacity and intestinal barrier in weaned piglets and IPEC-J2 cells - Wang, Meiwei; Huang, Huijun; Wang, Lei; Yin, Lanmei; Yang, Huansheng; Chen, Chiqing; Zheng, Qiankun; He, Shanping (Frontiers in Nutrition, 2022)
Tannic acid (TA), has raised widespread attention for its beneficial biological function with antioxidant capacity. This study investigated the protective role of TA on the intestinal antioxidant capacity and intestinal barrier in weaned piglets and porcine intestinal epithelial cells (IPEC-J2). A total of 18 weaned piglets were randomly allocated into two groups (n = 9) and fed with basal diet (control, CON) and basal diet containing 1000 mg/kg TA for two weeks. The in vivo results showed that TA treatment with TA increased both glutathione peroxidase (GSH-PX) activity and the protein expression of ZO-1 in the jejunum of weaned piglets, and reduced the level of malondialdehyde (MDA) in the serum and the mRNA and protein expression of Keap1 in the jejunum of weaned piglets. Furthermore, in vitro results indicated that TA treatment effectively alleviated tert-butyl hydroperoxide (TBH)-induced oxidative stress in IPEC-J2 cells, improved the antioxidant capacity through elevating the cell redox state and activating the Nrf2 pathway, and improved the intestinal barrier through upregulating the mRNA and protein expression of intestinal tight junction proteins and increasing the transepithelial electrical resistance (TEER) value. In conclusion, these results revealed that TA relieves oxidative injury and improves intestinal barrier function and intestinal antioxidant capacity through activating the Nrf2 signaling pathway. These findings suggest that TA has the potential application in alleviating oxidative stress in the intestine of weaned piglets.